Entry and competition of healthcare providers in Slovakia: A spatial analysis - Peter Mandézák; Martin Lábaj (University of Economics in Bratislava, Department of Economic Policy, 2020)
We study the relationship between market size and a number of firms in several healthcare professions in Slovakia to provide a new evidence about their entry decisions and a toughness of competition in the market. The size of a local market to support the entry of the first general practitioner is estimated to 1400 inhabitants. It equals 1700 inhabitants for the first pharmacy to enter, and 2300 for pediatricians. The population has to more than double for the second professional to enter. To support the second firm, the population per firm in the market has to increase by 30 % for pharmacies, by 25 % for general practitioners, and by almost 40 % for pediatricians. However, after the entry of the second firm, the intensity of competition does not change, except for pediatricians. The results are robust to spatial interactions taken into account. However, our estimates of spatial interactions show negative (but decreasing) spatial spillover effects for pharmacies, general practitioners, and dentists between 1995 and 2010. In this period, competitive effects prevailed and outweighed demand spillovers. We document that demand effect continued to grow since 2010 and in 2017 outweighed the competition effect for pharmacies.
Keywords: D22; I11; L22; R12; 330; entry models; healthcare market; industrial organization